Prevalence of tobacco, alcohol and psychoactive drug use among the college students in Chitwan - Pradhan, Manohar (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Students of colleges may be vulnerable to consume tobacco, alcohol and psychoactive drugs due to various factors. This study was conducted with objectives of determining the prevalence of smoking, alcohol and psychoactive drug use among the bachelor level college students of Chitwan. Materials & Methods: This is a descriptive cross sectional study among the 132 bachelor level students at various colleges of Bharatpur, Chitwan district of Nepal. The students were chosen by purposive sampling. A standard pre tested questionnaire was used to collect the data. Results: A total of 90 (68.2%) were males and 42 (31.8%) were females. The mean age was 22.2 ± 1.7 years. Seventy four (56.06%) responded that they had never consumed tobacco in any form.The number of cigarette smoked ranged from one to 20, with a mean of 7.85± 4.94 years. Forty eight (36.36%) never consumed alcohol and (87.87%) had never used psychoactive drugs.The most common motivator of the use of smoking, tobacco and psychoactive drugs was curiosity. Conclusion: The prevalence of smoking among the bachelor level students participating in our study was 43.94%, alcohol consumption was 63.63% and psychoactive drugs use was 12.12%.